Pachymeningitis With Dural Vessel Dilatation in MOG Antibody–Associated Disease: A Case Report - Huang, Yunchen; Song, Yafei; Liu, Ding; Liu, Yin (Case reports in neurological medicine, 2025)
Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) is a novel inflammatory demyelinating disorder marked by heterogenous clinical and radiological manifestations. Pachymeningitis is a rare manifestation. An 18-year-old male was hospitalized with fever, dizziness, altered consciousness, and seizure attacks. Serum testing was positive for MOG antibodies. Diffuse pachymeningitis with prominent dural vessel dilation was observed prior to treatment, which markedly improved after hormone therapy. MOGAD pachymeningitis with dural vessel dilatation broadens the imaging spectrum of MOGAD.